Global economic evaluation of oral cholera vaccine: A systematic review - Siew Li Teoh; Surachai Kotirum; Raymond C. W. Hutubessy; Nathorn Chaiyakunapruk (Taylor & Francis Group, 2018)
World Health Organization recommends oral cholera vaccine (OCV) to prevent and control cholera, but requires cost-effectiveness evidence. This review aimed to provide a critical appraisal and summary of global economic evaluation (EE) studies involving OCV to guide future EE study. Full EE studies, published from inception to December 2015, evaluating OCV against cholera disease were included. The included studies were appraised using WHO guide for standardization of EE of immunization programs. Out of 14 included studies, almost all (13/14) were in low- and middle-income countries. Most studies (11/14) evaluated mass vaccination program. Most of the studies (9/14) incorporated herd protective effect. The most common influential parameters were cholera incidence, OCV coverage, herd protection and OCV price. OCV vaccination is likely to be cost-effective when targeted at the population with high-risk of cholera and poor access to health care facilities when herd protection effect is incorporated and OCV price is low.